2020
DOI: 10.3389/fonc.2020.00357
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Myeloid BMPR1a Alters Differentiation and Reduces Mouse Prostate Cancer Growth

Abstract: The Bone Morphogenetic Protein (BMP) pathway is a member of the TGFβ signaling family and has complex roles in cancer. BMP signaling is rarely mutated and can be frequently overexpressed in many human cancers. The dichotomous role of BMPs as both tumor promoters and suppressors appears to be largely context based in both the cancer cell and the surrounding microenvironment. Myeloid cells including macrophages and neutrophils have been shown to be tumor promoting when stimulated from BMPs. We found that conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Ihle et al utilized a LysMCre-mediated myeloid-specific Bmpr1a conditional knockout mouse model along with a syngeneic prostate cancer model and demonstrated the pro-tumorigenic role of ALK3 in myeloid cells. They also confirmed that macrophage polarization is altered by ALK3 inhibition in this setting ( Ihle et al, 2020 ). BMP-7 is upregulated in tumors in a mouse model that does not respond to treatment with immune checkpoint inhibitors ( Cortez et al, 2020 ).…”
Section: Effect Of Bone Morphogenetic Proteins On Other Cellular Comp...mentioning
confidence: 55%
“…Ihle et al utilized a LysMCre-mediated myeloid-specific Bmpr1a conditional knockout mouse model along with a syngeneic prostate cancer model and demonstrated the pro-tumorigenic role of ALK3 in myeloid cells. They also confirmed that macrophage polarization is altered by ALK3 inhibition in this setting ( Ihle et al, 2020 ). BMP-7 is upregulated in tumors in a mouse model that does not respond to treatment with immune checkpoint inhibitors ( Cortez et al, 2020 ).…”
Section: Effect Of Bone Morphogenetic Proteins On Other Cellular Comp...mentioning
confidence: 55%
“…We currently demonstrate this phenomenon by examining pharmacologic inhibition of BMP signaling in distinct models of experimental bone metastasis with unique immune repertoires. Our previous findings that BMPR1a deletion in the myeloid LysMCre mouse model restricted primary prostate growth furthers the tumor promoting capacity that BMPs provide (31). However, in this current study the pharmacologic benefit to BMP inhibition was during engraftment of human cells lacking full immune functions (Figure 3).…”
Section: Discussionmentioning
confidence: 45%
“…A study focusing on prostate cancer found that loss of myeloid BMPR1α restricted tumor progression in a syngeneic mouse prostate cancer model. 43 It was also shown that deletion of BMPR1α in colon cancer could sensitize cells to chemotherapy and that high BMPR1α gene expression was correlated with decreased survival regardless of molecular breast cancer subtype. 44 , 45 Using transcriptomic profiling of isolated bone lining cell subtypes from a murine myeloma model, Gooding et al found that solubilized BMPR1α‐FC receptor‐ligand trap could prevent trabecular and cortical bone volume loss caused by myeloma.…”
Section: Discussionmentioning
confidence: 99%